2016
DOI: 10.1002/jcsm.12100
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional leucine supplementation attenuates cardiac failure in tumour‐bearing cachectic animals

Abstract: BackgroundThe condition known as cachexia presents in most patients with malignant tumours, leading to a poor quality of life and premature death. Although the cancer‐cachexia state primarily affects skeletal muscle, possible damage in the cardiac muscle remains to be better characterized and elucidated. Leucine, which is a branched chain amino acid, is very useful for preserving lean body mass. Thus, this amino acid has been studied as a coadjuvant therapy in cachectic cancer patients, but whether this treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…There are many animal models in which muscle loss is observed as a result of the disease development. There are numerous cancer cachexia animal model as cancer itself, [41][42][43][44][45] for the other chronic diseases, the literature shows animal model of sepsis, 46 chronic obstructive pulmonary disease, 47 chronic renal failure, 48 and chronic heart failure. 46,[49][50][51][52] However, these animal models are inadequate to be used as a rheumatoid cachexia animal model.…”
Section: Discussionmentioning
confidence: 99%
“…There are many animal models in which muscle loss is observed as a result of the disease development. There are numerous cancer cachexia animal model as cancer itself, [41][42][43][44][45] for the other chronic diseases, the literature shows animal model of sepsis, 46 chronic obstructive pulmonary disease, 47 chronic renal failure, 48 and chronic heart failure. 46,[49][50][51][52] However, these animal models are inadequate to be used as a rheumatoid cachexia animal model.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, the journal was seeing Cochrane reviews of the evidence base for interventions in cachexia and related fields coming through. 27,28 There was growing evidence for the development of clinical trials and for improvements in clinical trial methodology by the development and validation of clinical screening tools 29 and scoring systems, 30 biomarkers, 31,32 and evaluative methodologies, including the establishment of normal ranges. [12][13][14][15][16][17] In the area of translational studies in the mechanisms of cachexia, studies were published on expression of spliced skeletal muscle genes, 18 along with scientific evaluations of skeletal muscle physiology, 19,20 growth, wasting, 21-23 preservation, 24,25 and regeneration.…”
Section: By Methodologymentioning
confidence: 99%
“…26 Basic science approaches were also used to study the growing interest in the cardiac and cardio-metabolic effects of cancerrelated cachexia and of modern cancer therapies. 27,28 There was growing evidence for the development of clinical trials and for improvements in clinical trial methodology by the development and validation of clinical screening tools 29 and scoring systems, 30 biomarkers, 31,32 and evaluative methodologies, including the establishment of normal ranges. 33 These may help make trial design and novel treatment evaluation more precise in the future.The future pipeline of therapeutic interventions will be enhanced by the dissemination of basic reports into preclinical models [34][35][36][37] and early human trials 38 as a way of evaluating novel interventions.…”
mentioning
confidence: 99%
“…This is because cancer has significant effects on skeletal muscle, causing a catabolic state and resulting in widespread and progressive atrophy, including myocardial tissue. Studies have shown that cardiac atrophy can be a result of cancer evolution and its treatments [89][90][91]. These damages result in symptoms that can include breathlessness, lethargy, reduced exercise tolerance, congestive cardiac failure, and mortality [92].…”
Section: Myocardial Muscle In Cachexia and Leucinementioning
confidence: 99%